2020
DOI: 10.7759/cureus.6843
|View full text |Cite
|
Sign up to set email alerts
|

Violence Depicted in Superhero-Based Films Stratified by Protagonist/Antagonist and Gender

Abstract: The objective of this study was to describe and quantify acts of violence depicted in a select number of superhero-based films, further stratified by protagonist/antagonist characters and gender. A total of 10 superhero-based films released in 2015-2016 were analyzed by five independent reviewers. The average number of acts of violence associated with protagonist and antagonist characters for all included films was 22.7 and 17.5 mean events per hour, respectively (p=0.019). The average number of acts of violen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 27 publications
6
11
0
Order By: Relevance
“…Our finding that superheroes and villains did not significantly differ in the rates of violence portrayed is particularly troubling, given that violence was one the most common themes reported for both the superheroes and villains. These results parallel previous research reporting high levels of violence by male superheroes (e.g., Baker & Raney, 2007; Bauer et al, 2017) but contradict a study that found higher instances of violence in superheroes compared to villains (Muller et al, 2020). While our current analysis did not measure the effects of viewing the films, past research has found that exposure to superhero programming is associated with higher levels of weapon play in children (Coyne et al, 2014) and the American Academy of Pediatrics has issued a warning regarding exposure to violent media (Council on Communications and Media, 2009).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our finding that superheroes and villains did not significantly differ in the rates of violence portrayed is particularly troubling, given that violence was one the most common themes reported for both the superheroes and villains. These results parallel previous research reporting high levels of violence by male superheroes (e.g., Baker & Raney, 2007; Bauer et al, 2017) but contradict a study that found higher instances of violence in superheroes compared to villains (Muller et al, 2020). While our current analysis did not measure the effects of viewing the films, past research has found that exposure to superhero programming is associated with higher levels of weapon play in children (Coyne et al, 2014) and the American Academy of Pediatrics has issued a warning regarding exposure to violent media (Council on Communications and Media, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, endorsement of traditional masculine norms in emerging adult men is associated with childhood superhero identification (Roberts et al, 2021). Whereas, past research documents the prevalence of messages regarding masculinities in superhero programming (Baker & Raney, 2007; Burch & Johnsen, 2020; Miller et al, 2016), this research focuses primarily on the male superhero, who is altruistic and likable (Muller et al, 2020). Superheroes may promote resilience (Fradkin et al, 2016) or prosocial behaviors (Rosenberg et al, 2013), and it is often believed that superhero violence is acceptable or justified in order to achieve the greater good (Kort-Butler, 2012).…”
Section: Traditional and Toxic Masculinitiesmentioning
confidence: 99%
“…In stark contrast, Superman of today can be seen in the film Man of Steel violently ending his epic battle against his adversary, General Zod by gruesomely snapping his neck, which seemed reflective of the darker and more violent nature of superhero cinema in the modern era. Research presented at the 2018 American Academy of Pediatrics National Conference and Exhibition reported that, contrary to the popular belief, protagonists ("good guys") performed more acts of violence in their sample of superhero-based films compared with antagonists ("bad guys") [9]. An increase in violence is not only true for superhero-based films.…”
Section: Discussionmentioning
confidence: 88%
“…The list goes on: Catwoman, Luke Skywalker, Jessica Jones… There are few superheroes who do not rise from an humble or disadvantaged origin. In fact, approximately 50% had one parent murdered, 85% are orphans or have been abandoned and 29% had suffered from bullying (1,2).…”
Section: Dear Editormentioning
confidence: 99%
“…Resilience in superheroes often help them develop into what they are, and they are usually depicted as good and altruistic people. Some of this heroes may represent role models for children and youngers, which may promote resilience, especially in vulnerable children (1,2).…”
Section: Dear Editormentioning
confidence: 99%